Employee Turnover Intention in Indonesian Organizations: The Role of Job Satisfaction (A System Dynamics and Latent Dirichlet Allocation (LDA) Study) - Michelle Meily William; Didi Sundiman (Binus Business Review, 2025)
The research investigated employee turnover intention, a critical challenge for organizations, especially in Indonesia. The researchers focused on T and U Organizations, exploring the mediating role of job satisfaction. The descriptive data were gathered from ten informants, adopting a qualitative approach. Latent Dirichlet Allocation (LDA) was used to identify keywords from interviews, integrating these insights into a system dynamics model to simulate policies for improving employee retention. This unique NLP-driven integration offered a novel contribution. System dynamics methodology was extensively utilized to unravel complex, dynamic, and interdependent relationships within the system, offering a powerful approach to understanding intricate dynamics. Model simulations reveal a significant relationship. Increased job satisfaction effectively stabilizes turnover intentions. Key factors influencing job satisfaction include work environment, compensation, and job stress. Qualitative analysis also uncovers emergent factors, such as gender inequality in compensation and leader character, as crucial determinants. The research provides a valuable framework for understanding the intricate interplay between turnover intention and job satisfaction by offering practical insights for organizations and guiding future academic endeavors in the dynamic field of human resource management. The research also offers a robust and valuable tool for decision-makers to evaluate targeted policies aimed at enhancing job satisfaction and reducing turnover.